Klasifikasi Tingkat Kepuasan Pengguna dengan Menggunakan Metode SAW Pada Layanan PTSP - Indarti, Indarti; Wina Yusnaeni; Yoseph Tajul Arifin (LPPM Universitas Bina Sarana Informatika, 2025)
One Stop Integrated Service (PTSP) is one of the public service innovations that is expected to improve the quality of service to the community. However, various complaints are still found regarding the service. This study aims to classify the level of user satisfaction with PTSP services using the Simple Additive Weighting (SAW) method as a decision support system. Data were collected through a Google Form-based questionnaire distributed to 100 (one hundred) respondents in the DKI Jakarta area. The research stages include determining criteria, data normalization, weighting, calculating the final score, and classifying the level of satisfaction. The results of data processing that are included in the high satisfaction category are 37 (thirty-seven) or 59.68% of respondents, the average satisfaction category is 36 (thirty-six) respondents or 58.06%, and in the low satisfaction category are 27 (twenty-seven) respondents or 43.55%. This study also produces a web-based information system that is able to display graphs and criteria indexes to assist in periodic service evaluation. The developments in this study are expected to be the basis for continuous improvement in the PTSP service system.